Pengembangan Bahan Ajar Pendidikan Kesehatan melalui Media Powerpoint Interaktif Pembelajaran PJOK Sekolah Menengah Pertama - Subekti, Radik; Raharjo, Hermawan Pamot (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to produce a product for developing health education teaching materials through interactive media learning PJOK for Junior High Schools. This research is a development research or R&D which refers to the development of Borg & Gall. The data from the validation of learning experts got a percentage of 94% in the "very good" category. The data from the physical education expert validation results obtained a percentage of 86% in the "very good" category. Then the product was tested on a small scale with an average percentage result of 87% in the "very good" category. After that the product was revised by experts and declared very suitable for use. Then the product was tested on a large scale with an average percentage result of 90% in the "very good" category. The conclusion of this study is the development of health education teaching materials through interactive powerpoint media teaching materials products can be used as an alternative in learning physical education, sports and health (PJOK) offline or online for class VII students.